Living with fibromyalgia - Craggs-Hinton, Christine (London : Sheldon Press, 2019)
"Fibromyalgia is a chronic condition characterised by pain in the muscles, tendons, ligaments and nerves. Other symptoms include fatigue, sleep problems, allergies, anxiety, irritable bowel syndrome, headaches, morning stiffness and problems with short term memory and concentration. Increasing recognition of fibromyalgia means that diagnosis and treatment are increasingly likely, but self-help is still key. As well as tried and tested advice on how to reduce pain, boost energy levels and help with regular sleep, this new edition includes the latest in treatments, such as the popular therapy guaifenesin (sic). It also looks at how pain is experienced, explores the possibility that fibromylagia may be due to a rogue gene, and clarifies the difference between fibromyalgia and chronic fatigue syndrome. Other topics include: fibromyalgia and immune dysfunction; links with hypothyroidism; psychotherapy; the vital importance of low-impact aerobic exercise such as walking, cycling or swimming; diet; illustrated posture and exercise advice; pain and stress management; complementary therapies 'Having managed her own fibromyalgia, Christine now passes her experience and knowledge on to others so that they do not have to spend their precious time researching what she has already done. Progress has been made over the last few years and more medical professionals are recognising the symptoms, but there are still many who lack the knowledge to diagnose and treat fibromyalgia effectively. At present there are no national guidelines for treatment. This is one reason this book is so vital to those with fibromyalgia their families, friends and employers. -- Pam Stewart MBE, Fibromyalgia Association UK chair" -- ONIX annotation.
Previous edition: 2014.
Includes bibliographical references (page 164) and index.
108506
Keywords: Fibromyalgia -- Popular works; Fibromyalgia -- Treatment; Popular works